Vrijen met je sokken aan : homoseksuele mannen en condoomgebruik - Hoekzema, C.J.; van Hooren, M.M.P; Sandfort, Theo (Utrecht : Universiteit Utrecht, 1993)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie